Role of Tumor Microenvironment in the Risk of Thromboembolic Complications in Ovarian Cancer - A. S. Safonov; M. V. Zabelin; A. R. Uldashbaeva; L. I. Bashirova; R. O. Venidictov (Креативная хирургия и онкология)
Introduction. Incidence of ovarian cancer remains high in the overall prevalence of oncological pathology. Adjuvant chemotherapy refers to its treatment options. Patients with oncological pathology are faced with a high risk of thrombosis and thromboembolism, with up to 30% lethal outcome within a month of its development. A number of cancer cells are known to induce platelet aggregation, contributing to thrombosis and metastasis as a result of this interaction. Accordingly, the paper is aimed at presenting a clinical case for demonstrating the role of P-selectin expression in the complications in a patient with ovarian cancer. Materials and methods. The present paper evaluates platelet activation marker in a patient undergoing chemotherapy courses after cytoreductive surgery. Following the case conference and in accordance with the clinical recommendations of the Russian Oncology Association (AOR) and Russian Society of Clinical Oncology (RUSSCO), cytoreduction (CC-0), radical hysterectomy, transverse colectomy, left hemicolectomy with rectum resection were performed. The interventions included ascendostomy, pelvic, lateral right-sided and left-sided peritonectomy, pelvic lymphoadenectomy, total omentectomy, Renape-French HIPEC (hyperthermic intraperitoneal chemotherapy), abdominal and pelvic drainage. Expression of P-selectin on the platelet surface was measured as a marker of platelet activation. Results and discussion. At the time of admission, the patient had high CD62 expression activity compared to healthy volunteers (CD62 ADP- — 11.2%, CD62 ADP — 24.7% vs CD62 ADP- — 1.3%, CD62 ADP — 17.2%). During the complex treatment of ovarian cancer, the platelet activation increased (CD62 ADP- — 21.8 %, CD62 ADP+ — 30.1 %). At discharge, CD62 expression values reached the conditional norm, presumably indicating thrombosis development. Conclusion. Tumor microenvironment influences the hemostasis system. Detailed study into this issue obtains a high potential for the prevention of primary and secondary thromboembolic complications in oncologic patients.